Analisis Penerjemahan Metafora Bahasa Inggris Ke Dalam Bahasa Indonesia Pada Novel Vivaldis’s Virgin: Gadis-Gadis Vivaldi - Akhmad Hairul Umam (Wanastra: Jurnal Bahasa dan Sastra, 2017)
The objective of this research was to analyze and to get a deeper understanding toward metaphor translation, the equivalence between the source and target text as well as to investigate some factors that cause the equivalence including method, procedure, and semantic structure of translated metaphor. Metaphor as the object of this research was taken from a novel, Vivaldi’s Virgin written by Barbara Quick. The novel was translated into Indonesian: Gadis-gadis Vivaldi by Abdullah Al-wazin and published by Maroon Books Publisher in 2008. Each metaphor had different methods and procedures for its translation.  A method used by the researcher on this translation text study was content analysis through descriptive qualitative method. There were 162 metaphors taken from this novel and classified into three categories: (1) metaphor translated as metaphor, (2) metaphor translated as a simile, (3) simile translated as a simile. Based on this data, the researcher found 110 text of metaphors translated into metaphors, 21 metaphors translated into simile and 31 of similes translated into simile. Each metaphor which was made up of different collocations has different image and equivalent. However, the reseach proved that this work had enought equivalent particularly between the source and target text. Translator of this novel mostlly used modulation and preposition method which was very much close to the naturalness of the target text.Keywords: Translation, metaphor, simile, equivalent.